The Role of Fermented Vegetables as a Sustainable and Health-Promoting Nutritional Resource - Borrego Ruíz, Alejandro; González-Doménech, Carmen María; Borrego-García, Juan José (MDPI, 2024)
The increasing global burden of morbidity and mortality from chronic diseases related to poor diet quality, coupled with the unsustainable depletion of vital planetary resources by current food production systems, threatens future food security and highlights the urgent need to transition to high-quality plant-based diets as a viable solution to mitigate economic, health, and environmental challenges. Taking into consideration the significant role that fermented vegetables may play as a sustainable, healthy, long-lasting, and plant-based nutritional resource, this narrative review analyzes their production and benefits. For this purpose, the mechanisms of the fermentation process are explored, along with the importance of probiotic cultures in plant-based fermented foods, and with the implications of fermentation on food safety within the broader framework of low-impact, organic, plant-derived nutrition. Additionally, the health benefits of fermented vegetables and probiotics are examined, including their effects on mental health. Vegetable fermentation is a versatile method for enhancing food preservation, nutritional quality, and safety. This ancient practice prolongs the shelf life of perishable items, reduces the toxicity of raw ingredients, and improves digestibility. Specific starter cultures, particularly lactic acid bacteria, are essential for controlling fermentation, ensuring safety, and maximizing health benefits. Fermented vegetables, rich in probiotics, support gut health and immune function. Emerging research indicates their potential to alleviate adverse mental health symptoms such as stress and anxiety, highlighting their significance in modern dietary guidelines and chronic health management.
Keywords: Fermentación; Fermented Vegetables; Sustainability; Health; Fermented food